A novel strategy to restore power systems after a great blackout: The Argentinean case - Alvarez, Gonzalo Exequiel (2021)
This paper presents a multi-objective mathematical model to perform power restoration. It considers simultaneously the objective functions: restoration time, load shedding, and cost. New formulations are developed to improve the maneuverability of the system elements. This distinguishes the novel proposal from the rest of the one or two objective approaches. The linear nature of the formulation allows for obtaining feasible solutions within efficient times. The proposal includes in the main objective function the social view in terms of prioritize the restitution of the system for as many users as possible. It enables using this proposal to restore large scale systems. Results indicate that more equitable and faster restoration solutions can be obtained than the reported one in the mentioned case.